Work life balance : Perspective of generation Y - Zaiton, Hassan; Dayang Kartini, Abang Ibrahim; Sheilla Lim, Omar Lim (2011)
This study was conducted for the purpose of identifying the perspective of Generation Y in Work Life Balance. Specifically, this study examined on the different types of work life balance policies preferred by students of Generation Y and their level of preferences. This study was based on a sample survey of 182 third year undergraduate students in Human Resource Development program and was asked to complete a voluntary self administered questionnaire. The findings indicated that Generation Y regard work life balance as important to a person’s quality of work, job performance and long term job satisfaction. Flexible working arrangement, pregnancy and leave related are the three significant policies chose by the respondents in this study